Clinical decision support and beyond : progress and opportunities in knowledge-enhanced health and healthcare - Greenes, Robert A., 1940-; Del Fiol, Guilherme (Academic Press, 2023)
"Clinical Decision Support and Beyond: Progress and Opportunities in Knowledge-Enhanced Health and Healthcare, now in its third edition, discusses the underpinnings of effective, reliable, and easy-to-use clinical decision support systems at the point of care as a productive way of managing the flood of data, knowledge, and misinformation when providing patient care. Incorporating CDS into electronic health record systems has been underway for decades; however its complexities, costs, and user resistance have lagged its potential. Thus it is of utmost importance to understand the process in detail, to take full advantage of its capabilities. The book expands and updates the content of the previous edition, and discusses topics such as integration of CDS into workflow, context-driven anticipation of needs for CDS, new forms of CDS derived from data analytics, precision medicine, population health, integration of personal monitoring, and patient-facing CDS. In addition, it discusses population health management, public health CDS and CDS to help reduce health disparities. It is a valuable resource for clinicians, practitioners, students and members of medical and biomedical fields who are interested to learn more about the potential of clinical decision support to improve health and wellness and the quality of health care. Presents an overview and details of the current state of the art and usefulness of clinical decision support, and how to utilize these capabilities Explores the technological underpinnings for developing, managing, and sharing knowledge resources and deploying them as CDS or for other uses Discusses the current drivers and opportunities that are expanding the prospects for use of knowledge to enhance health and healthcare"--